c-Myc protein expression is not an independent prognostic predictor in cervical squamous cell carcinoma - Brenna,S.M.F. (2002)
The c-myc protein is known to regulate the cell cycle, and its down-regulation can lead to cell death by apoptosis. The role of c-myc protein as an independent prognostic determinant in cervical cancer is controversial. In the present study, a cohort of 220 Brazilian women (mean age 53.4 years) with FIGO stage I, II and III (21, 28 and 51%, respectively) cervical squamous cell carcinomas was analyzed for c-myc protein expression using immunohistochemistry. The disease-free survival and relapse-rate were analyzed using univariate (Kaplan-Meier) survival analysis for 116 women who completed the standard FIGO treatment and were followed up for 5 years. Positive c-myc staining was detected in 40% of carcinomas, 29% being grade 1, 9% grade 2, and 2% grade 3. The distribution of positive c-myc according to FIGO stage was 19% (17 women) in stage I, 33% (29) in stage II, and 48% (43) in stage III of disease. During the 60-month follow-up, disease-free survival in univariate (Kaplan-Meier) survival analysis (116 women) was lower for women with c-myc-positive tumors, i.e., 60.5, 47.5 and 36.6% at 12, 36, and 60 months, respectively (not significant). The present data suggest that immunohistochemical demonstration of c-myc does not possess any prognostic value independent of FIGO stage, and as such is unlikely to be a useful prognostic marker in cervical squamous cell carcinoma.